HEXANESOLUBLE BIOACTIVE COMPONENTS OF LEAF EXTRACT OFQUINOA - I. H. Khan; A. Javaid (Journal of Animal and Plant Sciences, 2022)
Aim of the present study was to identify various bioactive constituents present in non-polar n-hexane fraction of methanolic leaf extract of quinoa (Chenopodium quinoa Willd.), a crop of family Chenopodiaceae. Quinoa leaves were extracted in methanol. After evaporation of the solvent, the residues were mixed with distilled water, partitioned with n-hexane in a separating funnel and were analyzed by GC-MS, which showed presence of 15 constituents including 10 bioactive components namely 9,12-octadecadien-1-ol, (Z,Z)- (31.31%), 1-(+)-ascorbic acid 2,6-dihexadecanoate (17.39%), 9,12,15-octadecatrienoic acid, methyl ester, (Z,Z,Z)- (12.99%), hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl) ethyl ester (4.84%), phytol (5.01%), tetradecanoic acid (5.34%), hexadecanoic acid, methyl ester (8.04%), octadecanoic acid (2.98%), 2-pentadecanone, 6,10,14-trimethyl- (1.20%), and octadecanoic acid, methyl ester (0.99%). Literature survey revealed that these compounds exhibit a wide variety of biological properties including antifungal, antibacterial, antioxidant, anticancer, anti-inflammatory, nematicidal and others. This study concludes that n-hexane fraction of methanolic leaf extract of quinoa is a rich storehouse of bioactive molecules and can be used for treatment of a number of ailments.
Keywords: Antimicrobial; bioactive compounds; Chenopodium quinoa; leaf extract